2019
DOI: 10.1111/cbdd.13640
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of prolyl hydroxylase 2 inhibitors with new chemical scaffolds as in vivo active erythropoietin inducers through a combined virtual screening strategy

Abstract: Hypoxia-inducible factor (HIF) is identified to be a promising target to mediate the response to hypoxia. Its stability and activation are negatively controlled by prolyl hydroxylase 2 (PHD2). Thus, PHD2 inhibition has been perceived as a promising anti-anemia therapy. In this study, we carried out a structure-based virtual screening followed by in vitro and in vivo biological validation, with the goal to identify novel PHD2 inhibitors. As a result, a set of hits with new chemical scaffolds were revealed to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Dihydro‐1,2,4‐triazolo[1,5 ‐a ]pyrimidine 45 (Figure 13) was selected as a potential PHD2 inhibitor from the commercial compound database by a structure‐based virtual screening strategy combined with pharmacophore modeling and molecular docking. However, biological evaluations showed that the potency of compound 284 (IC 50 =12.79±0.38 μM) was lower than that of the approved drug roxadustat (IC 50 =0.59±0.02 μM) [334] …”
Section: Partially Hydrogenated Azolopyrimidines In Drug Designmentioning
confidence: 96%
See 1 more Smart Citation
“…Dihydro‐1,2,4‐triazolo[1,5 ‐a ]pyrimidine 45 (Figure 13) was selected as a potential PHD2 inhibitor from the commercial compound database by a structure‐based virtual screening strategy combined with pharmacophore modeling and molecular docking. However, biological evaluations showed that the potency of compound 284 (IC 50 =12.79±0.38 μM) was lower than that of the approved drug roxadustat (IC 50 =0.59±0.02 μM) [334] …”
Section: Partially Hydrogenated Azolopyrimidines In Drug Designmentioning
confidence: 96%
“…However, biological evaluations showed that the potency of compound 284 (IC 50 = 12.79 � 0.38 μM) was lower than that of the approved drug roxadustat (IC 50 = 0.59 � 0.02 μM). [334]…”
Section: Metabolic Disorders Controlmentioning
confidence: 99%
“…In the latter study, although the concentration of 50 μM was found to be inhibitory, in another study, 57 this concentration was found to be suitable for stabilizing HIF-1α, therefore, for better angiogenesis. While these amounts of the drug were investigated on the cellular impact, in a study, 58 the inhibitory role of FG-4592 with different concentrations of prolyl hydroxylase 2 (PHD2) was directly investigated. It was seen that by increasing the concentration up to 150 μM, the inhibitory role also increases, but the generalization of this response to the cellular role of the drug cannot be correct.…”
Section: Release Study Of Fg-4592 From Pthfmentioning
confidence: 99%
“…As one application of this assay may be for a highthroughput screen for inhibitors of PHDs, we performed a proof-of-concept experiment by testing whether it is sensitive enough to detect known PHD2 inhibitors in ongoing clinical trials. At present, there are a number of small-molecule inhibitors of PHD2 in ongoing clinical trials to treat CKDinduced anemia (47). We selected three commercially available inhibitors in current phase 3 trials to evaluate the sensitivity of the 2,4-DNPH α-KG assay: Vadadustat (AKB-6548 from Akebia, approved in Japan), Roxadustat (FG-4592 from FibroGen, approved in Japan and China), and Daprodustat (GSK1278863 from GSK).…”
Section: Determining Ic 50 Values Of Phd2 Inhibitors In Clinical Trials With the 24-dnph α-Kg Assaymentioning
confidence: 99%